2012
DOI: 10.4067/s0716-97602012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Variation in concentrations of major bioactive compounds in Prunella vulgaris L. related to plant parts and phenological stages

Abstract: Prunella vulgaris L. (Labiatae) contains a variety of structurally diverse natural products, primarily rosmarinic acid (RA), ursolic acid (UA) and oleanolic acid (OA), which possess a wide array of biological properties. In the present study, P. vulgaris was harvested at three developmental stages (vegetative, full-flowering and mature-fruiting stages), dissected into stem and leaf tissues and assayed for chemical contents using high performance liquid chromatography. Signifi cant changes in the concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 23 publications
2
40
0
1
Order By: Relevance
“…The maximum oil production and yield is from flowering plants (maybe due to activation of several enzymes necessary to the biosynthesis of some components) and with closest spacing, respectively (Badi et al, 2004;Chauhan et al, 2013;Sellami et al, 2009). For example, a study of Chen et al (2012) indicates Table 2 Effects of essential oil samples from S. lavandulifolia on cytoprotective enzyme activity in PC12 cells. Cells were treated with essential oil samples (50 and 15 μg/mL) for 24 h, followed by incubation with H2O2 (0.1 mM) for 30 min.…”
Section: Discussionmentioning
confidence: 95%
“…The maximum oil production and yield is from flowering plants (maybe due to activation of several enzymes necessary to the biosynthesis of some components) and with closest spacing, respectively (Badi et al, 2004;Chauhan et al, 2013;Sellami et al, 2009). For example, a study of Chen et al (2012) indicates Table 2 Effects of essential oil samples from S. lavandulifolia on cytoprotective enzyme activity in PC12 cells. Cells were treated with essential oil samples (50 and 15 μg/mL) for 24 h, followed by incubation with H2O2 (0.1 mM) for 30 min.…”
Section: Discussionmentioning
confidence: 95%
“…P. vulgaris has been identified as one of the most promising potential medicinal and edible wild plant resources [5]. The fresh leaves of young plants are popular for use in a wild vegetable recipe in southeast China [4], whereas its mature plants are commonly used as a traditional medicinal herb in some Asian and Europe countries, such as China [6], Korea [7], Japan [8], Turkey [9], the Czech Republic [10], Poland [11] and Germany [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical investigations have revealed that P. vulgaris contains a variety of bioactive constituents, primarily rosmarinic acid (RA), ursolic acid, and oleanolic acid. 14,15) RA, an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid, is a main active constituent of P. vulgaris, is accumulated constitutively, and is one of the most common polyphenolic compounds in plants. 16) It was first isolated and characterized the compound and named it for the plant from which it was isolated, rosemary (Rosmarinus officinalis).…”
mentioning
confidence: 99%